Collagen-Based Wound Dressings: Innovations, Mechanisms, and Clinical Applications - Adina Alberts; Andreea Gabriela Bratu; Adelina-Gabriela Niculescu; Alexandru Mihai Grumezescu (Gels)
Collagen-based wound dressings have developed as an essential component of contemporary wound care, utilizing collagen’s inherent properties to promote healing. This review thoroughly analyzes collagen dressing advances, examining different formulations such as hydrogels, films, and foams that enhance wound care. The important processes by which collagen promotes healing (e.g., promoting angiogenesis, encouraging cell proliferation, and offering structural support) are discussed to clarify its function in tissue regeneration. The effectiveness and adaptability of collagen dressings are demonstrated via clinical applications investigated in acute and chronic wounds. Additionally, commercially accessible collagen-based skin healing treatments are discussed, demonstrating their practical use in healthcare settings. Despite the progress, the study discusses the obstacles and restrictions encountered in producing and adopting collagen-based dressings, such as the difficulties of manufacturing and financial concerns. Finally, the current landscape’s insights indicate future research possibilities for collagen dressing optimization, bioactive agent integration, and overcoming existing constraints. This analysis highlights the potential of collagen-based innovations to improve wound treatment methods and patient care.